Colour Preferences For Icon Design In Graphical User Interface - Lim, Yan Peng (2009)
The aim of this study is to examine the icon and background colour preferences of users of graphical user interfaces. The study investigates specific icon colour preferences against different background colours using the framework of the RGB colour model (Paynton, 2004)